Gender and Community-Based Tourism: Theoretical Debates from a Decolonial Perspective - Alejandra de María Hernández-González; Pilar Espeso-Molinero (Tourism and Hospitality)
This paper critiques the Western-centric lens in gender studies, emphasising the need for decolonial, intersectional, and inclusive methodologies in community-based tourism (CBT) research. It argues that universalist narratives often overlook local power structures, gendered labour divisions, and socio-economic inequalities, disregarding localised knowledge and the structural barriers that shape women’s realities in tourism. In the case of rural women, these dominant perspectives fail to address key issues such as the unequal distribution of benefits, the complexities of tourism participation, and the tensions between market demands, social change, and cultural preservation. This paper calls for context-sensitive approaches that amplify women’s voices and lived experiences in CBT. It highlights the urgency of decolonising knowledge, challenging hegemonic epistemologies that homogenise women’s experiences and reinforce Eurocentric gender norms. The study also underscores intersectionality as a crucial tool to expose the overlapping systems of oppression—including ethnicity, class, race, and access to global tourism markets—that deepen gender inequalities in CBT. Without a decolonial and intersectional lens, tourism studies risk reproducing extractivist logics that marginalise local voices and perpetuate inequitable structures. Future research must move beyond Western frameworks, fostering more ethical, sustainable, and socially just approaches to gender studies in tourism.